2013
DOI: 10.1136/acupmed-2012-010270
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment of Phantom Limb Pain and Phantom Limb Sensation in a Primary Care Setting

Abstract: A 45-year-old man presented with phantom limb pain and phantom limb sensation 12 weeks after an above-elbow amputation of his right arm. He underwent seven sessions of acupuncture at weekly intervals carried out by his general practitioner on his intact left arm, with complete relief of the phantom limb pain and considerable improvement of the phantom limb sensation of his right arm. This case demonstrates the possible benefits from the use of short acupuncture sessions for a potentially chronic condition unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…91 Even difficult cases of phantom limb pain had been treated with acupuncture. 92 It can ease the discomfort some subjects feel while waiting for knee surgery, and it may even be considered as an alternative to surgery in some cases. As with any other form of health care, however, one needs to remember that not all patients will respond to acupuncture.…”
Section: Alternative Medicine Approachesmentioning
confidence: 99%
“…91 Even difficult cases of phantom limb pain had been treated with acupuncture. 92 It can ease the discomfort some subjects feel while waiting for knee surgery, and it may even be considered as an alternative to surgery in some cases. As with any other form of health care, however, one needs to remember that not all patients will respond to acupuncture.…”
Section: Alternative Medicine Approachesmentioning
confidence: 99%
“…Most modalities use physical energy for their therapeutic effect, including heat, cryotherapy (cold), TENS (transcutaneous electrical nerve stimulation), and acupuncture. While TENS and acupuncture are not universally accepted as systems for the management of neuropathic and phantom pain, numerous reports have demonstrated the effectiveness of acupuncture in these areas [5153] while a recent study showed a mean reduction in pain intensity scores of 1.8 at rest and 3.9 on movement in five patients after just 60 min of TENS [54]. Each patient in the latter study had either phantom pain, residual limb neuropathic pain, or both.…”
Section: Pain Managementmentioning
confidence: 99%
“…The use of CAM including acupuncture, hypnosis, deep-breathing exercise, massage therapy, meditation, naturopathy, yoga, mind-body system, dietary interventions and fasting, as well as herbal medicine has been increasing since more than 10 years [52][53][54][55][56][57]. As chronic pain affects the whole person (body, mind and spirit), the CAM therapies in combination with more traditional therapies could allow the patient to take care of himself at multiple levels and to actively participate in his own healing process and wellbeing.…”
Section: Discussionmentioning
confidence: 99%